Investigation on interlaminar shear strength properties of disc laser machined consolidated CF-PPS laminates (eXPRESS Polymer Letters, 2011)
In consequence of an increased interest in using endless carbon fibre reinforced thermoplastic composites (TPC), automated and highly productive processing technologies for cutting and trimming steps of consolidated materials are sought. In this paper, the influence on the thermal effect caused by laser cutting with respect to static strength properties of TPC based on a polyphenylene sulfide (PPS) matrix is studied. For the cutting experiments, consolidated TPC laminates at varying thicknesses up to s = 3.1 mm and a disc laser emitting at a wavelength of λ = 1030 nm at a maximum output power of PL = 2 kW are used. For the first time, the resulting magnitude of the heat affected zone (HAZ) at the cutting edge of the composite material is correlated with interlaminar shear strength tests. The results are compared to specimens prepared by milling and abrasive water jet cutting. Depending on the laminate thickness, the laser treated TPC samples show comparable properties to those of conventionally processed specimens. A reduced load bearing area, as a consequence of damaged fibre-matrix-adhesion due to laser impact, is identified as main factor for the reduction of interlaminar shear strengths for higher laminate thicknesses.